0.1 Second versus 0.2 Second pulse duration of Frequency Doubled Nd: YAGLaser in treatment of Clinically Significant Diabetic Maculopathy. - Al-Quriashi, Najah K.; Essa, Samar O. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: clinically significant macular edema (CSME) is the commonest cause of visual loss in patients with diabetes mellitus and laser focal photocoagulation is the golden standard for treating it. Patients and Methods: A frequency doubled Nd: YAG laser was used to treat all eyes included in this study with diabetic maculopathy. Thirty eyes of three insulin dependent and twenty six non insulin dependent diabetic Iraqi patients were included. The study involved twenty six males, three females and followed for one year. Their ages were ranging between 36- 59 years, all of them from patients attending ophthalmic out-patient department in the medical city in the period between January 2005 and June 2006. Eyes divided in to two groups (fifteen eyes in each group) and the disease severity was taken into account. The first group treated with 0.1 second and second group with 0.2 second pulse duration. Results: In group (1) improvement of V.A occurred in 19.99% (Statistically significant) and 60% (Statistically significant) in group (2). There was stabilization 80% (Statistically insignificant) in group (1) and 33.33% Stabilization (Statistically significant) in group (2), while worsening only in group (2) 6.67%(Statistically insignificant). Conclusion: The frequency doubled Nd:YAG laser is effective in controlling diabetic macular oedema when applied in focal treatment. The setting of 100μm 0.2sec., pulse exposure time show more improvement in V.A. than 100μm 0.1sec.